The community structure of mangroves in Libertad, Antique. - Tibubos, Braex Louie Talimay
Mangrove forests are unique intertidal ecosystems that are primarily found on relatively sheltered coastlines, deltas, estuaries , and lagoons in tropical and subtropical regions of the world. This study was conducted to assess the community structure of mangroves in Nypa River, Barangay Tinigbas, Barangay Tabok, Purok 1-Centro, Brangay Union, and Barangay Centro Weste, Libertad, Antique, using the transect line method. Specifically, it aims to determine selected physical and chemical factors such as salinity, pH, temperature for water and soil as well as characterization of the substrate; identify and classify mangrove species present in the area; and describe the community structure in terms of stand basal area, stems per hectare, relative frequency, relative dominance, importance value, Shannon index of diversity, zonation patterns, seedling and sapling density. No study has been done to document the community structure of mangroves in Libertad, Antique thus, this study was done to provide vital information needed for its proper management. Six stations were selected in Libertad, Antique. Sixteen (16) species of true mangroves were identified belonging to ten (10) families: Acanthaceae - Acanthus ebracteatus, Acanthus ilicifolius and Acanthus volubilis; Avicenniaceae - Avicennia marina and Avicennia rumphianar; Combretaceae - Lumnitzera racemosa; Euphorbiaceae - Excoecaria agallocha;Meliaceae - Xylocarpus granatum; Myrsinaceae - Aegiceras floridum; Palmae - Nypa fruiticans; Rhizophoraceae - Bruguiera sexangula, Rhizophora apiculata, Rhizophora mucronata and Rhizophora stylosa; Sonneratiaceae - Sonneratia alba and Sterculiaceae - Heritiera littoralis. The study area had a water salinity range of 3.78 ppt to 29.86 ppt; water temperature range of 27.33 degrees centigrade to 31.32 degrees centigrade; water pH range of 6.64 to 7.69; soil temperature range of 29.40 degrees centigrade to 31.46 degrees centigrade; and soil pH range of 5.18 to 7.46. Basal area ranges from 0.0016 m2/ha for Rhizophora stylosa to 113.461 m2/ha for Sonneratia alba. The species with the highest average of stems per hectare was Sonneratia alba with 6400 as well as the highest average density value of 26.167. Station 5 had the highest density and the lowest density and lowest was Station 3. sonneratia alba had the highest relative frequency of 14.946 percent occurrence. From the sixteen mangrove species recorded, Sonneratia alba had the highest relative dominance of 243.808 and the least was Avicennia rumphiana with a rleative dominance value of 1.739. The most important species was Sonneratia alba with 302.409 and the least was Rhizophora mucronata with 5.521. The area is considered to be lowly diverse with 0.399 Shannon Index of Diversity. On the per plot basis of the Index of Diversity, Station 3 had the highest with 0.438 and Station 5 had the lest with 0.069. The structure of mangroves in this area is influenced by physico-chemical factors like substrate type (i.e., rocky, sandy and muddy); location and type of mangroves (i.e., narrow coastal fringing type) and human activities (i.e., reforestation, cutting, etc.)